Creating the Conditions for Geographic Conceptual Development in Post-Primary Students through Collaborative Guided Inquiry - Jeana Kriewaldt; Lucy Robertson; Natasha Ziebell (MDPI AG, 2023)
This paper explores the potential for a collaborative guided inquiry task to stimulate geographic thinking using core geographic concepts of 'location', 'distance and direction', 'scale', 'symbols', 'relative location' and 'slope and topography.' The guided inquiry began with a visit to a park, with students then applying geographic thinking to redesign the park in a way that optimised utility for various user groups. The data generated included student work samples and video recordings of student groups as they worked through the task. The results show that the task design facilitated a deeper understanding of geographic concepts, including spatial relationships, connections and interactions. Furthermore, the collaborative nature of the task prompted students to use skills of explaining, negotiating and justifying their decisions. A critical feature of this analysis is the role that the teacher has in providing specialised guidance to support geographic thinking based on the needs of each group. The study highlights the value of practical, real-world experiences in geography education to learn, discuss and explore geographic concepts, enabling development of critical thinking, reasoning and problem-solving skills.